2016
DOI: 10.1111/muse.12125
|View full text |Cite
|
Sign up to set email alerts
|

Museums as Therapeutic Environments and the Contribution of Art Therapy

Abstract: Although healthcare interventions—including those targeting mental health problems—are usually delivered in clinics and hospitals, nowadays the museum sector has come to play an important role in improving health and well‐being, enhancing the development of social inclusion and challenging discrimination. This paper explores the ways in which art therapy can be applied in the museum field and how, with the assistance of art therapists, museum spaces can become therapeutic holding environments that help individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Future work could specifically consider contemplative motivations and experiences with regard to their impact on resulting subjective, transformative experiences. Further, given recent research that has shown that museum visits have well-being benefit (e.g., Ioannides, 2016;Mastandrea, Fagioli, & Biasi, 2019;Thomson, Lockyer, Camic, & Chatterjee, 2017), it would be interesting to consider the role of the different types of exhibition experiences relative to perceived well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Future work could specifically consider contemplative motivations and experiences with regard to their impact on resulting subjective, transformative experiences. Further, given recent research that has shown that museum visits have well-being benefit (e.g., Ioannides, 2016;Mastandrea, Fagioli, & Biasi, 2019;Thomson, Lockyer, Camic, & Chatterjee, 2017), it would be interesting to consider the role of the different types of exhibition experiences relative to perceived well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Art therapy has been shown to possess enhanced healing potential in promoting mental health through partnerships with museums and galleries (March et al, 2004). Museums address health issues by providing "non-traditional instructional services, gaining a vital role in community connection, " (Ioannides, 2016;Thaler et al, 2017) which has been confirmed by the art psychotherapy program at EMST (National Museum of Contemporary Art Athens). Research has revealed that museum collections increase participants' self-esteem, confidence, and creativity.…”
Section: Research Status Of Museum Art Therapymentioning
confidence: 99%
“…Froggett and Trustram (2014) relate this to Winnicott's (1971) idea of 'potential space' and this is supported by Salom, who discusses how 'visitors' inner frameworks interact with external reality to process events, create relationships, identify subjective experience and conjure intimate meaning' (Salom, 2013, p. 4). Museums have also been considered as 'holding environments' (Ioannides, 2017;Salom, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be said that museum settings and their collections allow for greater exploration than the usual clinical settings, and for both intimacy and independence through possibilities for closeness and distance (Salom, 2008). The way people inhabit, discover and explore the spaces can give insight into the style of relating to ourselves, others and the environment (Chamberlain, 2020;Ioannides, 2017;Jury, 2020a;Salom, 2008Salom, , 2011Trustram, 2013). Young female participants in a study by Coles and Harrison (2018) reported enjoying the option of moving around collectively and/or individually, with the opportunity for playfulness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation